What is appropriate surveillance for metal-on-metal hip arthroplasty patients? - Matharu, G; Judge, A; Eskelinen, A; Murray, D; Pandit, H (Taylor and Francis, 2017)
The unexpected high revision rates of large-diameter (femoral head sizes of 36 mm or greater) metal-on-metal hip arthroplasties (MoMHAs) have led to worldwide regulatory authorities recommending regular surveillance, even for asymptomatic individuals. However, these recommendations are not evidence-based and are very costly. The rapidly evolving evidence base requires an update regarding the investigation and management of MoMHA patients. This article is the first of 2 (the second article in this series will consider the threshold for performing revision, and the outcomes following ARMD revision surgery: Matharu et al., Revision surgery of metal-on-metal hip arthroplasties for adverse reactions to metal debris: A clinical update. Acta Orthop 2018; in press), and considers the various investigative modalities used during surveillance, with specific focus on blood metal ion sampling and cross-sectional imaging. No single investigation can universally be used during MoMHA patient surveillance. Recent studies have now provided important information on interpreting blood metal ions (effective in identifying patients at low risk of problems), clarifying the roles of cross-sectional imaging (reserve combined ultrasound and MARS-MRI for complex cases), and providing parameters to safely exclude many asymptomatic patients from regular surveillance. This information will be useful when designing future surveillance protocols for MoMHA patients.